Everything you Always Wanted to Know About Inventors (But Never Asked): Evidence from the PatVal-EU Survey - Dietmar Harhoff; Karin Hoisl (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2006)
Based on a survey of the inventors of 9,017 European patented inventions, this paper provides new information about the characteristics of European inventors, the sources of their knowledge, the importance of formal and informal collaborations, the motivations to invent, and the actual use and economic value of the patents.
urn:nbn:de:bvb:19-epub-1261-5
Keywords: J24; O31; O34; 650; inventor; patent; incentives; innovation; patent system; patent value